2012
DOI: 10.1016/j.jallcom.2012.02.155
|View full text |Cite
|
Sign up to set email alerts
|

MgyNi1−y(Hx) thin films deposited by magnetron co-sputtering

Abstract: Abstract:In this work we have synthesised thin films of Mg y Ni 1-y (H x ) metal and metal hydride with y between 0 and 1. The films are deposited by magnetron co-sputtering of metallic targets of Mg and Ni. Metallic Mg y Ni 1-y films were deposited with pure Ar plasma while Mg y Ni 1-y H x hydride films were deposited reactively with 30% H 2 in the Ar plasma. The depositions were done with a fixed substrate carrier, producing films with a spatial gradient in the Mg and Ni composition. The combinatorial method… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…1(d) could be attributed to the (110) peak of the monoclinic LT phase, suggesting the existence of that phase prior to the first step of annealing. This is in agreement with what reported previously by Mongstad et al [16] who observed signs of a monoclinic structure in a TEM study of reactively sputtered thin films, which were found to be amorphous by XRD. The presence of the (110) peak of LT phase confirms that not all of the crystallites have taken the cubic HT phase as preferred.…”
supporting
confidence: 93%
“…1(d) could be attributed to the (110) peak of the monoclinic LT phase, suggesting the existence of that phase prior to the first step of annealing. This is in agreement with what reported previously by Mongstad et al [16] who observed signs of a monoclinic structure in a TEM study of reactively sputtered thin films, which were found to be amorphous by XRD. The presence of the (110) peak of LT phase confirms that not all of the crystallites have taken the cubic HT phase as preferred.…”
supporting
confidence: 93%
“…Although the films are found to be amorphous for XRD with Cu Kα radiation, our earlier work has showed that crystallites of monoclinic Mg 2 NiH 4 are observable with transmission electron microscopy (TEM) [20]. The crystal size found with TEM was 5-10 nm [20].…”
Section: Synthesis and Structural Properties Of The Filmsmentioning
confidence: 88%
“…This is not very surprising since a very thin intermediate oxide layer would be difficult to detect on a glass substrate due to the low refractive index contrast. [20]. We have do not presented the data for samples with y < 1.9 and y > 2.4 because the optical absorption for these films was high below the band gap, and thus suggesting high presence of metallic particles.…”
Section: Optical Properties and Layeringmentioning
confidence: 99%
See 1 more Smart Citation
“…Here again, extra care should be taken regarding the elemental composition of the deposited materials as it might depend on the position where the elemental analysis is made on the substrate, especially if a spatially resolved analysis is carried out by a technique such as scanning (transmission) electron microscopy combined with energy-dispersive X-ray spectroscopy (S(T)EM-EDS). Typical examples of the formation of compositional gradients on coated surfaces can be found, for example, in [ 54 55 ]. Further control on film chemistry is obtained through reactive (magnetron) sputtering.…”
Section: Reviewmentioning
confidence: 99%